Performance differences between the arched and flat bench press in beginner and experienced paralympic powerlifters - Ribeiro, N. F.; Dorneles, J. R.; Luna, R. M.; Spina, M. A.; Gonçalves, C. W.; Gomes Costa, R. R. (The Journal of Strength and Conditioning Research, 2022)
The present study aimed to verify the differences of the total load, trajectory of the barbell in the sagittal plane, and mean velocity of the barbell between the arched and flat techniques of the bench press in beginner (BG) and experienced (EG) Paralympic powerlifters. Twenty beginners (age: 34.4 years; experience: 3.3 months) and 23 experienced (age: 35.5 years; experience: 9.8 months) Paralympic powerlifters were selected from a Rehabilitation Hospital Network and a Paralympic sports center. Subjects were assessed in the one-maximum repetition test of the bench press exercise using the flat and arched bench press techniques (48-72-hour interval between sessions). Maximum strength, trajectory of the barbell in the sagittal plane, and mean velocity of the barbell were measured to compare the techniques and the groups. The total load corrected with the Haleczko formula was significantly higher in EG compared with BG (Delta = 21.1%; effect sizes [ES] = 0.39, p = 0.05). There were no significant differences for all analyzed outcomes comparing the arched and flat techniques. During the eccentric phase of the bench press, all assessed differences ranged from -16.6 to 23.1% and presented ES of trivial to moderate. On the concentric phase, the assessed differences ranged from -20.7 to 13.9% and presented ES of trivial to moderate. The total load, trajectory of the barbell in the sagittal plane, and mean velocity of the barbell were not significantly different between the arched and flat techniques for experienced and beginner powerlifting athletes during both the eccentric and concentric phase of the movement. However, further analyses are essential to determine the best technique for athletes.